Corrosion control and design of cathodic protection system for steel gas pipeline / Aziram Mat Salleh and Rosdi Baharuddin - Mat Salleh, Aziram; Baharuddin, Rosdi (1999)
Corrosion has been classified in many different ways. One method recommended by Fontana is to divide corrosion into low-temperature and high temperature corrosion. Another separates corrosion into direct^combination (or oxidation) and electro chemical corrosion. The preferred classification here is (1) wet corrosion and (2) dry corrosion. Wet corrosion occurs when a liquid is present. This usually involves aqueous solutions or electrolytes and accounts for the greatest amount of corrosion by far. A common example is corrosion of steel by water. Dry corrosion occurs in the absence of a liquid phase or above the dew point of the environment. Vapors and gases are usually the corrodents. Dry corrosion is most often associated with high temperatures. An example is attack on steel by furnace gases.